In search of mediators of leadership behavior to Team Creativity in Team Start-ups - Antonio, Tony; Indrianto, Agoes Tinus Lis; Padmawidjaja, Liestya (Frontiers in Psychology, 2022)
Creativity is believed as the first step to Innovation especially in a team or workgroup in organization. Team Creativity will lead to several innovations in a team such as product innovation dan process innovation. Team leaders play a great role in embracing Team Creativity. Our study investigates the mediator variables to foster the impact of leadership behaviour to Team Creativity in Team Start-up. Earlier research shows that two value-based leadership styles, Transformational and Servant leadership, are significantly give impact to the creativity in a team. We proposed two mediators to foster the Team Creativity namely Team Climate and Team Ambidexterity. The sample are early team start-ups in several cities in Indonesia, run and led by young people. It is an empirical cross sectional quantitative research with more than 434 participants which aggregated into 145 teams. The result shows that Team Climate and Team Ambidexterity are good mediators of Servant and Transformational leadership behaviours to Team Creativity in Team Start-ups. The two variables maximize the impact of leadership behaviour to Team Creativity.